VIDEO BLOGGING TO IMPROVE STUDENS’ SPEAKING PERFORMANCE - Alpha ThessaLika R.M. Butar Butar; Sudarsono Sudarsono; Zainal Arifin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This research was aimed to improve students’ speaking performance by using videoblogging to Year 11 Students of SMAK Immanuel Pontianak especially on E class inacademic year 2018/2018. It was focused to improve their fluency and accuracy by usingvideo blogging as media. The research design of this study was classroom action research.The 38 students of class XI E were participating in this research. The researcher observedthe students’ improvement in speaking by collecting data through observation checklist,field notes and speaking test. The students’ attitude towards the learning process wasgathered by observation checklist and field note. The data of speaking was obtained byspeaking test which was assessed through scoring rubric. Based on the data, the studentsshowed improvement in the process of speaking. In the cycle I, they were already great inpresenting the materials but some of the students were still making some pauses and wrongpronounciation. The researcher conducted the cycle II which resulted that, the studentscould speak more fluently and accurately by gathering and listening the information fromthe media. The students also got motivation to speak during the teaching and learningactivity. From all of the result, it can be inferred that video blogging improve students’speaking performance.. Key Words: Classroom Action Research, Improve, Speaking, Video Blogging